Harnessing the eccrine sweat glands for the management of interdialytic weight gain – a pilot study - Zaher A. Armaly; Yaacov Nitzan; Gil Chernin; Doron Aronson (Renal Failure)
Hemodialysis patients are susceptible to excess volume accumulation, particularly over the 2-day interval (long interdialytic gap), resulting in higher interdialytic weight gain (IDWG). We thought to determine whether a novel device designed to enhance fluid and salt loss by activating the eccrine sweat glands can mitigate IDWG. Patients eligible for the study were undergoing regular hemodialysis for ≥3 months, without residual renal function, and with IDWG (as a percentage of IDWG/dry body weight) ≥2.5%. Treatments were administered at the patient’s home. The primary performance endpoint was differences in weight gain over long interdialytic period with the device compared to the control period. Secondary exploratory endpoints included the need for ultrafiltration (UF) rate > 10 mL/kg/h in the post-interval dialysis. Five patients were enrolled into the pilot study (age range 26 to 69 years, 3 women). The hourly mean weight loss from sweat was 186 ± 45 g/h. The average procedure length was 4.5 h with an average fluid loss of 899 ± 283 grams per procedure. The average least-squares mean absolute difference of IDWG between the control and treatment periods was −2.0%; (95% confidence interval [CI], −2.9% to −1.2%, p < 0001). The reduction in IDWG was associated a reduction in UF rates, from 9.23 ± 3.7 mL/kg/h to 5.55 ± 2.45 mL/kg/h between the control and treatment periods (p < 0.001), resulting in a safe UF rate (<10 mL/kg/h) in all post-treatment sessions. We conclude that enhancing sweat rate can mitigate IDWG in hemodialysis patients.